Learning from patients the science of medicine - Bert Vogelstein, lecturer; Huda Y. Zoghbi, lecturer; Ann DeStefano Sutherland, producer; Wally Ashby, director (Howard Hughes Medical Institute, 2004)
Medical researchers discuss how working with patients has influenced their efforts to understand and treat cancers and neurological disorders.